Functional and Genomic Characterization of Ligilactobacillus salivarius TUCO-L2 Isolated From Lama glama Milk: A Promising Immunobiotic Strain to Combat Infections - Quilodrán-Vega, Sandra; Albarracin, Leonardo; Mansilla, Flavia; Arce, Lorena; Zhou, Binghui; Islam, Md Aminul; Tomokiyo, Mikado; Al Kassaa, Imad; Suda, Yoshihito; Kitazawa, Haruki; Villena, Julio (Frontiers in Microbiology, 2020)
Potential probiotic or immunobiotic effects of lactic acid bacteria (LAB) isolated from the milk of the South American camelid llama (Lama glama) have not been reported in published studies. The aim of the present work was to isolate beneficial LAB from llama milk that can be used as potential probiotics active against bacterial pathogens. LAB strains were isolated from llama milk samples. In vitro functional characterization of the strains was performed by evaluating the resistance against gastrointestinal conditions and inhibition of the pathogen growth. Additionally, the adhesive and immunomodulatory properties of the strains were assessed. The functional studies were complemented with a comparative genomic evaluation and in vivo studies in mice. Ligilactobacillus salivarius TUCO-L2 showed enhanced probiotic/immunobiotic potential compared to that of other tested strains. The TUCO-L2 strain was resistant to pH and high bile salt concentrations and demonstrated antimicrobial activity against Gram-negative intestinal pathogens and adhesion to mucins and epithelial cells. L. salivarius TUCO-L2 modulated the innate immune response triggered by Toll-like receptor (TLR)-4 activation in intestinal epithelial cells. This effect involved differential regulation of the expression of inflammatory cytokines and chemokines mediated by the modulation of the negative regulators of the TLR signaling pathway. Moreover, the TUCO-L2 strain enhanced the resistance of mice to Salmonella infection. This is the first report on the isolation and characterization of a potential probiotic/immunobiotic strain from llama milk. The in vitro, in vivo, and in silico investigation performed in this study reveals several research directions that are needed to characterize the TUCO-L2 strain in detail to position this strain as a probiotic or immunobiotic that can be used against infections in humans or animals, including llama.